Tumor risk markers in recurrent respiratory papillomatosis - Caroline Fernandes Rimoli; Rogerio Hamerschmidt; Evaldo Dacheux de Macedo Filho; Vanessa Mazanek Santos; Lucas Resende Lucinda Mangia; Bettina Carvalho (Brazilian Journal of Otorhinolaryngology, 2023)
Objectives: This study aims to investigate the pattern of immunoexpression of proteins p16, p53 and Ki-67 in RRP, as well as to evaluate its influence on the number of surgeries that patients have undergone to date and to analyze the benefit of immunohistochemistry in this disease. Methods: Clinical-demographic data and tumor samples were obtained from 33 patients with RRP. The expression of proteins p16, p53 and Ki-67 was analyzed by immunohistochemical method. Results: Most patients had already undergone more than one surgery. The p16 marker was negative in 24.2% of the cases, with little positivity in 27.3% of the cases, moderate in 36.4% and intense in 12.1%. The p53 marker was positive in all cases, with little immunoexpression in 39.4% of cases, moderate in 36.4% and intense in 24.2%. The Ki-67 marker showed nuclear positivity in all lesions, although in varying degrees, with a mean proliferative index ± SD (standard deviation) of 51.7 ± 26. Conclusions: The papillomatous lesions had varying degrees of immunoexpression of proteins p16, p53 and Ki-67, but no specific immunohistochemical pattern was observed. It was found, with statistical difference, that the number of surgeries was higher in cases with greater intensity of p53 expression, without correlation with the other markers. The benefit of immunohistochemistry in recurrent respiratory papillomatosis may lie in the prognostic assessment. However, further studies are needed to evaluate the use of this technique for this purpose. Level of evidence: : 4.